The Role of AKT3 Copy Number Changes in Brain Abnormalities and Neurodevelopmental Disorders: Four New Cases and Literature Review - Lopes, Fátima; Torres, Fátima; Soares, Gabriela; van Karnebeek, Clara D.; Martins, Cecília; Antunes, Diana; Silva, João; Muttucomaroe, Lauren; Botelho, Luís Filipe; Sousa, Susana; Rendeiro, Paula; Tavares, Purificação; et al. (Frontiers in Genetics, 2019)
Microdeletions at 1q43-q44 have been described as resulting in a clinically recognizable phenotype of intellectual disability (ID), facial dysmorphisms and microcephaly (MIC). In contrast, the reciprocal microduplications of 1q43-q44 region have been less frequently reported and patients showed a variable phenotype, including macrocephaly. Reports of a large number of patients with copy number variations involving this region highlighted the AKT3 gene as a likely key player in head size anomalies. We report four novel patients with copy number variations in the 1q43-q44 region: one with a larger deletion (3.7 Mb), two with smaller deletions affecting AKT3 and SDCCAG8 genes (0.16 and 0.18 Mb) and one with a quadruplication (1 Mb) that affects the entire AKT3 gene. All patients with deletions presented MIC without structural brain abnormalities, whereas the patient with quadruplication had macrocephaly, but his carrier father had normal head circumference. Our report also includes a comparison of phenotypes in cases with 1q43-q44 duplications to assist future genotype-phenotype correlations. Our observations implicate AKT3 as a contributor to ID/development delay (DD) and head size but raise doubts about its straightforward impact on the latter aspect of the phenotype in patients with 1q43-q44 deletion/duplication syndrome. Keywords: 1q43-q44 CNVs; AKT3; Microcephaly; Macrocephaly; ZBTB18; SDCCAG8; phenotypic expressivity